Software de automatización de registros de pago de los usuarios del sistema de riego carrizal-Chone en la ciudad de Calceta - Loor Valencia, Gina Elizabeth (2013)
The developing of an automation software for payment records and facilitated the data collection, we developed and implemented a software system for the Carrizal-Chone irrigation system in the city of Calceta. Using the V - Model, also called life cycle analysis to performed the functional processes through visits to the people working in this office, by which it was determined that the management processes required more control. To create the system, we used tools such as Visual Studio.Net 2010, with a program of layers (data, business, presentation) to obtain the separation of business logic and logic design. The data layer is deposited where the database was created in SQL Server 2012, required from the business layer in which received requests and responses by the users are sent after the running process. The installation and commissioning of the desktop software, in conjunction with the staff of the organization, validated the software allowed satisfactory results such as reduction of registration time by 90% and control over information generated throughout the overall management of Carrizal-Chone irrigation system.